The Effect of Syrian Climate Coast On The Stability of Aspirin - هبه سليمان (Latakia University Journal -Medical Sciences Series, 2024)
Aspirin is a commonly used medicine. It is used routinely in older people to prevent heart attacks. This is due to its anti-platelet effect. However, it is known to show an allergy problem and its destruction under the influence of moisture which will turn it into salicylic acid which causes stomach irritations and maybe ulcer, This calls for studying the stability of aspirin tablets. The aim of this study is to determine the effect of the coastal climate on the stability of aspirin, tablets made by three national companies and available in the local market, from both the physical side ( hardness and fragility), and chemical side ( content level). The study was conducted on the tablets in their commercial format in the market, and within the medicine portfolio under different storage conditions (either on the shelf or via a speeding study). Constitutional methods in regard to the hardness and fragility of the tablets were adopted! Whereas, TLC and Spectrophotometer methods were adopted to calibrate the content of aspirin. The causes that lead to the damage of aspirin were also addressed. The low concentration of aspirin was observed for legally constitutionally permitted percentages after 180, 30 and 90 days for the tablets manufactured by company A , Company B and company C, respectively, as for the marketed product. Whereas, the concentration in aspirin decreased in the tablets which were placed in the portfolio after 3 days in regard to the tablets made by company A , 2 days for the other two companies (B, C). As for storing the tablets under the conditions 75% RH, 40 ° C and 75% RH, 25 ° C, the concentration was decreased in the tablets of all three companies ( A, B, C) after 15 days. There were left in the blister, but those which were kept in the clipboard, the concentration dropped in one day Upon studying the stability in both conditions 60% RH, 40 ° C and 60% RH, 25 ° C, the results were comparable to those results from the storage on the shelf, whether, in the blister or in the clipboard. Studying the hardness and fragility of the aspirin tablets, it became clear that the hardness has been decreased while the hardness of the studied condition has been increased. This decreased of the tablets was larger in regard to the tablets placed in the portfolio, while the fragility has increased significantly in the extreme storage conditions in the clipboard.